Brain and muscle energy metabolism studied in vivo by 31P-magnetic resonance spectroscopy in NARP syndrome. Issue 12 (December 1994) - Lodi, R; Montagna, P; Iotti, S; Zaniol, P; Barboni, P; Puddu, P; Barbiroli, B
Abstract : Phosphorus magnetic resonance spectroscopy (31P-MRS) was used to study in vivo the energy metabolism of brain and skeletal muscle in two members of an Italian pedigree with NARP syndrome due to a point mutation at bp 8993 of mtDNA. In the youngest patient, a 13 year old girl with retinitis pigmentosa, ataxia, and psychomotor retardation, there was an alteration of brain energy metabolism shown by a decreased phosphocreatine content, increased [ADP] and decreased phosphorylation potential. The energy metabolism of her skeletal muscle was also abnormal, as shown by resting higher inorganic phosphate and lower phosphocreatine concentrations than in normal subjects. Her mother, a 41 year old woman with minimal clinical involvement, showed a milder derangement of brain energy metabolism and normal skeletal muscle. Findings with MRS showed that this point mutation of mtDNA is responsible for a derangement of energy metabolism in skeletal muscle and even more so in the brain.